'Massilimalia timonensis' sp. nov., a new bacterium species isolated from human faeces after decontamination with alcohol. (January 2018) - Afouda, P.; Dubourg, G.; Cadoret, F.; Fournier, P.E.; Raoult, D.
Abstract: We describe the main characteristics of a new bacterial species ' Massilimalia timonensis ' sp. nov. The type strain Marseille-P3753 T (=CSUR P3753) was isolated from the stool of a healthy Senegalese man.